2018
DOI: 10.1186/s12917-018-1430-3
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey in wild boar (Sus scrofa) in Switzerland and other European countries: Sarcoptes scabiei may be more widely distributed than previously thought

Abstract: BackgroundSarcoptic mange has recently emerged in wild boar in Switzerland, raising the question of the origin of the infection. The main aim of this study was to assess the extent of exposure of the wild boar populations to Sarcoptes scabiei in Switzerland, prior to and after the detection of mange cases, to determine whether the mite has been recently introduced into the populations concerned. We performed a serological survey using a commercially available ELISA and 1056 archived blood samples of free-rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Mild infection in animals is characterized by pruritic papules, erythema, scales and alopecia, whereas the main sign in chronic cases is skin thickening due to hyperkeratosis and/or exudative crusts formation ( Rahman et al., 2010 ). In Spain, sarcoptic mange has been reported in several game species including the Iberian ibex ( Capra pyrenaica ) ( León-Vizcaíno et al., 1999 ), Southern chamois ( Rupricapra pyrenaica parva ) ( Fernández-Morán et al., 1997 ), roe deer ( Capreolus capreolus ) ( Oleaga et al., 2008a ), red deer ( Cervus elaphus ) ( Oleaga et al., 2008b ), wild boar ( Sus scrofa ) ( Haas et al., 2018 ), red fox ( Vulpes vulpes ) ( Gortázar et al, 1998 ), European wild rabbit ( Oryctolagus cuniculus ) ( Millán, 2010 ), and the introduced European mouflon ( Ovis aries musimon ), fallow deer ( Cervus dama ) and Barbary sheep ( Ammotragus lervia ) ( Iacopelli et al., 2020 ; Moroni et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mild infection in animals is characterized by pruritic papules, erythema, scales and alopecia, whereas the main sign in chronic cases is skin thickening due to hyperkeratosis and/or exudative crusts formation ( Rahman et al., 2010 ). In Spain, sarcoptic mange has been reported in several game species including the Iberian ibex ( Capra pyrenaica ) ( León-Vizcaíno et al., 1999 ), Southern chamois ( Rupricapra pyrenaica parva ) ( Fernández-Morán et al., 1997 ), roe deer ( Capreolus capreolus ) ( Oleaga et al., 2008a ), red deer ( Cervus elaphus ) ( Oleaga et al., 2008b ), wild boar ( Sus scrofa ) ( Haas et al., 2018 ), red fox ( Vulpes vulpes ) ( Gortázar et al, 1998 ), European wild rabbit ( Oryctolagus cuniculus ) ( Millán, 2010 ), and the introduced European mouflon ( Ovis aries musimon ), fallow deer ( Cervus dama ) and Barbary sheep ( Ammotragus lervia ) ( Iacopelli et al., 2020 ; Moroni et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other diagnostic methods, the detection of antibodies allows retrospective epidemiological studies on stored samples, permitting comparison within and among areas (Haas et al 2018). Immunodiagnostic methods have been a key tool in revealing the presence of Sarcoptes scabiei in hosts and zones where it was only suspected or not confirmed by mite identification (Haas et al 2018). This is particularly relevant for host species that are elusive and difficult to detect visually in the field and in host species where mange may be asymptomatic or cause only mild lesions.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed S. scabiei mite mitochondrial 16S rDNA by TaqMan real-time PCR ( 4 ) in the sampled horse, ox, goat, and fox but not in the sampled sheep, cat, dogs, or pigs. Analyses with a panel of 9 microsatellites (sarms 33, 35–38, 40, 41, 44, and 45) ( 5 ) confirmed that foxes were the source of the mites (Figure, panel F); the mites on the outbreak farm were similar to each other and to mites previously collected from foxes in Switzerland ( 6 ) but different from those collected from wild ungulates in Spain, Switzerland, France, and Italy ( 5 , 7 , 8 ).…”
mentioning
confidence: 76%